Gender transformative approach in CGIAR Research Program 3.1 on Aquatic Agricultural Systems - Shaw, Alison; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Context: The approach is currently being adopted in the implementation of the CGIAR Research Program on Aquatic Agricultural Systems. The approach encourages critical awareness of gender roles and norms among men and women, challenges the distribution of resources and allocation of duties between men and women, and promotes the position of women while addressing power relationships between women and others in the community (Interagency Gender Working Group, USAID). The CCAFS Smart Farm (SF) Project and Aquatic Agricultural Systems (AAS) are looking at strategies to address climate-related challenges. They are exploring viable gender-differentiated strategies to enhance the resilience, productivity and diversity of aquaculture systems in weather and water challenged contexts, including differentiated research needs in improving fish circulation, homestead pond management with women and integrating farming systems such as homestead vertical agriculture systems. The goal is ultimately to simultaneously help women and men farmers and fisherfolk increase their adaptive capacity and livelihoods. Worldfish as a whole is interested in gender transformative approaches to minimize vulnerabilities experienced by socially differentiated users.